THE INFLUENCE OF ORTHODONTIC TREATMENT ON DENTAL ARCH PARAMETERS IN CHILDREN WITH UNILATERAL NONUNION OF LIP, ALVEOLAR PROCESS AND PALATE TO URANOPLASTY - D. A. DOMENYUK; M. P. PORFYRIADIS; G. M.-A. BUDAYCHIEV; E. G. VEDESHINA; S. V. DMITRIENKO (Кубанский научный медицинский вестник, 2017)
With the help of biometric studies of the jaw models, 75 children with congenital blindness of the hard palate during the period of the bite of the milk teeth before and after the conducted orthodontic treatment studied the dynamics of changes in the individual sizes of the dental arches of the upper, lower jaw, and also the hard palate. The result of the orthodontic treatment with capping expanding devices on the upper jaw to uranoplasty was an increase in the frontal-retromolar and transverse dimensions of the dental arches between the dairy canines and molars, as well as the width of the hard palate at the level of the dairy canines and second molars. Changes in the parameters of the dental arches of the lower jaw, as well as the height of the hard palate, were statistically not reliable.